Career flexibility and its relation to time perspective: a study with college students in the Portuguese context - Frainer, Juliana; Janeiro, Isabel N. (Frontiers in Psychology, 2023)
The volatility of the labor market resulting from globalization, rapid technology changes, economic competition, and the impact of events such as the Covid-2019 Pandemic, demand from vocational psychology a more refined understanding of the processes individuals face while dealing with those new challenges and opportunities, especially in uncertain contexts. Theories such as Planned Happenstance address constructs such as career flexibility, an essential skill to recognize, create and use chance events as career opportunities. Furthermore, when fortuitous events and uncertain contexts are considered for career development, it becomes relevant to understand how subjective time perspective evolves, that is how the life events and career goals are projected, accessed, valued, and organized. Given this context, the objectives of the present study are to adapt and validate a Portuguese version of the Career Flexibility Inventory (Kim, 2019), and to explore the possible relationships between career flexibility, time perspective, and variables inherent to the educational context. The Portuguese version of the Career Flexibility Inventory, the Time Perspective Inventory and a sociodemographic form were answered by 1,380 students from Portuguese higher education institutions. The results indicated that the Portuguese version of the CFI has an adequate three-factor structure with good reliability indices. Some limitations regarding psychometric validity show the importance of further research to improve the measure. However, the findings contribute to theoretically and operationally deepening discussions on the multidimensionality of Career Flexibility. The results regarding the relationships between time perspective and career flexibility seem to be in line with the theoretical indicators of the variables and support the formulated hypotheses, specifically, that future orientation presents a positive correlation with active adaptation; a negative correlation with wavering, and wavering presents a positive correlation with the negative future orientation. The results partially support the hypothesis of differences on time perspective and career flexibility among students with different academic grade averages and from diverse scientific area of study. Finally, the study advances a theoretical reflection on the different nature of career flexibility dimensions and contributes to broadening and promoting theoretical and operational discussions on the relationships between time perspective and career flexibility, which are still incipient.